2011
DOI: 10.1042/bj20110304
|View full text |Cite
|
Sign up to set email alerts
|

Structure and activity of the Saccharomyces cerevisiae dUTP pyrophosphatase DUT1, an essential housekeeping enzyme

Abstract: Genomes of all free-living organisms encode the enzyme dUTPase (dUTP pyrophosphatase), which plays a key role in preventing uracil incorporation into DNA. In the present paper, we describe the biochemical and structural characterization of DUT1 (Saccharomyces cerevisiae dUTPase). The hydrolysis of dUTP by DUT1 was strictly dependent on a bivalent metal cation with significant activity observed in the presence of Mg2+, Co2+, Mn2+, Ni2+ or Zn2+. In addition, DUT1 showed a significant activity against another pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…dUTP is a non-canonical nucleotide formed in the cell as a side product of dTTP formation. dUTPase is an essential enzyme expressed by the cell to decrease the concentration of dUTP, thus preventing incorporation of dUMP into genomic DNA (19). This result suggests that SAMHD1 also contributes to maintenance of the cellular dUTP concentration.…”
Section: Samhd1 Allosteric Activation By Dgtp Derivatives-to Testmentioning
confidence: 57%
“…dUTP is a non-canonical nucleotide formed in the cell as a side product of dTTP formation. dUTPase is an essential enzyme expressed by the cell to decrease the concentration of dUTP, thus preventing incorporation of dUMP into genomic DNA (19). This result suggests that SAMHD1 also contributes to maintenance of the cellular dUTP concentration.…”
Section: Samhd1 Allosteric Activation By Dgtp Derivatives-to Testmentioning
confidence: 57%
“…The reaction products (ADP and ATP) were analyzed using reversed phase chromatography on a Varian ProStar HPLC system equipped with a Varian Pursuit C18 column as previously described [37, 38]. Standard solutions of AMP, ADP, and ATP were used to confirm the identity of the observed peaks and products.…”
Section: Methodsmentioning
confidence: 99%
“…2c) to those observed in form I, with the only difference being the manner in which the cubes pack against one another. Furthermore, in the 24-mer asymmetric unit (in space group P1) of yeast apo dUTPase (Tchigvintsev et al, 2011) we identified a similar cube but again with different packing between adjacent cubes within the crystal lattice. The yeast dUTPase cube does not superpose exactly on those of the B. subtilis dUTPases, reflecting some distortion of the intra-cube molecular packing (Fig.…”
Section: Form Ii: Cubes In Crystals Of Homotrimeric Dutpasesmentioning
confidence: 92%
“…Four of the motifs are contributed by two adjacent subunits, while motif V, which is located in a flexible C-terminal arm, originates from the third subunit and caps the active site, alternating between closed and open states along the reaction cycle. This C-terminal arm is disordered in most of the published structures, only adopting an ordered conformation in M. tuberculosis dUTPase in complex with Mg 2+ -dUpNHpp , FIV dUTPase in complex with dUDP (Prasad et al, 2000), the human dUTPase complexes with dUMP, dUDP and dUTP and a recent structure of the yeast dUTPasedUMP complex (Tchigvintsev et al, 2011). Motif V is the least understood motif and has been the subject of several recent studies (Pé csi et Bacillus subtilis is a model organism for Gram-positive bacteria and plays a role in industrial processes through its ability to produce and secrete large amounts of proteins such as amylases and proteases (Harwood, 1992).…”
Section: Introductionmentioning
confidence: 97%